'I Respect My Imam, But I Can't Fight Even if He Tells Me to Fight. I am Peaceful for Myself and My Family': Are We Overestimating Religion in Peace Dynamics?. Issue 2 (3rd April 2021) - Ossai, Emmanuel Chiwetalu
ABSTRACT: Religious actors and works on religious peacebuilding largely hold that religion can have an impact, either positive or negative, on peace between members of different religious groups. However, questions about the extent of this impact remain. Guided by an interpretive research paradigm, using a case study design, and observing relevant tenets of other qualitative approaches, the author conducted fieldwork in Abuja, Nigeria, from January to August 2019, in an attempt to understand the impact of religious leaders, religious peace norms and religious peace activism on the relative peace existing there. Primary data were collected through in-depth interviews with 17 religious leaders, as well as observation, focus group discussions and interviews with over 73 lay Christians and Muslims. The study shows that religious factors impact on interreligious peace, but not in the manner that religious elites and some commentators on religious peacebuilding often hold. Consideration of evidence from other (conflict and post-conflict) settings shows that the impact of religious factors varies with context and so a key question is the reasons for such variations. After highlighting this, the article considers other major implications of the study for interreligious relations and religious peacebuilding.